Chemoradiotherapy with and without deep regional hyperthermia for squamous cell carcinoma of the anus - Ott, Oliver J.; Schmidt, Manfred; Semrau, Sabine; Strnad, Vratislav; Matzel, Klaus E.; Schneider, Ignaz Hans Friedrich; Raptis, Dimitrios; Uter, Wolfgang; Grützmann, Robert; Fietkau, Rainer (Strahlentherapie und Onkologie, 2018)
PURPOSE: To compare results after chemoradiotherapy with and without deep regional hyperthermia in patients with anal cancer. METHODS: Between 2000 and 2015, a total of 112 consecutive patients with UICC stage I-IV anal cancer received chemoradiotherapy with 5‑fluororuracil and mitomycin C (CRT). In case of insufficient tumor response 4-6 weeks after chemoradiotherapy, patients received an interstitial pulsed-dose-rate brachytherapy boost. Additionally, 50/112 patients received hyperthermia treatments (HCRT). RESULTS: Median follow-up was 41 (2-165) months. After 5 years follow-up, overall (95.8 vs. 74.5%, P = 0.045), disease-free (89.1 vs. 70.4%, P = 0.027), local recurrence-free (97.7 vs. 78.7%, P = 0.006), and colostomy-free survival rates (87.7 vs. 69.0%, P = 0.016) were better for the HCRT group. Disease-specific, regional failure-free, and distant metastasis-free survival rates showed no significant differences. The adjusted hazard ratios for death were 0.25 (95% CI, 0.07 to 0.92; P = 0.036) and for local recurrence 0.14 (95% CI, 0.02 to 1.09; P = 0.06), respectively. Grades 3-4 early toxicities were comparable with the exception of hematotoxicity, which was higher in the HCRT group (66 vs. 43%, P = 0.032). Incidences of late side effects were similar with the exception of a higher telangiectasia rate in the HCRT group (38.0 vs. 16.1%, P = 0.009). CONCLUSION: Additional regional hyperthermia improved overall survival, local control, and colostomy rates. Its potential beneficial role has to be confirmed in a prospective randomized setting. Therefore, the HyCAN trial has already been established by our group and is currently recruiting patients (Clinicaltrials.gov identifier: NCT02369939).
EVALuna2:36451